2016
DOI: 10.1002/aenm.201601372
|View full text |Cite
|
Sign up to set email alerts
|

MXene‐on‐Paper Coplanar Microsupercapacitors

Abstract: coplanar interdigitated electrode architecture and shorter paths for in-plane diffusion of electrolyte ions are expected to exhibit improved power and rate capabilities over the conventional electrode designs. [4,5] Such architecture can also be simply integrated on the same substrate as other electronic components such as sensors or rectifiers. However, most of the efforts have been focused on fabricating microsupercapacitors on rigid and flexible substrates employing conventional microfabrication techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
277
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 417 publications
(282 citation statements)
references
References 50 publications
3
277
2
Order By: Relevance
“…[44] Figure 2e shows the X-ray diffraction (XRD) patterns of the Ti 3 AlC 2 MAX-phase raw powder and as-prepared 2D few-layered Ti 3 C 2 T x flakes. [53,54] Additionally, the Ti 3 C 2 T x surfaces are terminated by functional groups such as O, OH, and F. Additionally, the (002) peak shifted from ≈10° to ≈6°, and the corresponding peak intensity was stronger, indicating the successful preparation of 2D few-layered Ti 3 C 2 T x flakes.…”
Section: Mxene/bc Composite Papers: Preparation Strain Engineering mentioning
confidence: 99%
See 2 more Smart Citations
“…[44] Figure 2e shows the X-ray diffraction (XRD) patterns of the Ti 3 AlC 2 MAX-phase raw powder and as-prepared 2D few-layered Ti 3 C 2 T x flakes. [53,54] Additionally, the Ti 3 C 2 T x surfaces are terminated by functional groups such as O, OH, and F. Additionally, the (002) peak shifted from ≈10° to ≈6°, and the corresponding peak intensity was stronger, indicating the successful preparation of 2D few-layered Ti 3 C 2 T x flakes.…”
Section: Mxene/bc Composite Papers: Preparation Strain Engineering mentioning
confidence: 99%
“…All the curves exhibit good rectangular consistency, revealing the excellent conductivity of the electrodes and capacitive behavior of these MSC units. [51][52][53][54][55] In particular, the areal capacitance is an order of magnitude higher than that of carbon material-based planar MSCs (0.1-10 mF cm −2 ). Moreover, as shown in the GCD curves of the asfabricated standard MSC units measured at the same current charge-discharge density (Figure 4j The available areal capacitance (mF cm −2 ) and energy density (mWh cm −2 ) provided per standardized MSC unit could be calculated from the GCD curves ( Figure S4a represent 132% enhancement compared to those based on pure MXene paper (85.13 mF cm −2 and 0.00419 mWh cm −2 ).…”
Section: Standardized Msc Units: Fabrication and Electrochemical Perfmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] However, symmetric supercapacitor devices based on Ti 3 C 2 T x have shown limited operating voltage windows (≈0.6 V) because Ti 3 C 2 T x is prone to oxidation at higher anodic potentials (for example, anodic oxidation was observed in a symmetric two-electrode configuration at ≥0.6 V). [19,20] Recently, it has been shown that Ti 3 C 2 T x MXene electrodes are electrochemically stable in acidic electrolyte at higher cathodic potentials when metal current collectors are replaced by hydrogen overpotential materials, such as glassy carbon or graphite foil. [9] This resulted in a wider negative potential window operation of Ti 3 C 2 T x MXene electrodes (up to −1.1 V vs Hg/Hg 2 SO 4 ), [9] unlike the previous studies with a limited potential window.…”
mentioning
confidence: 99%
“…The performance of the Ti 3 C 2 T x -based microsupercapacitors SCs obtained in this way is obviously better than those from conventional methods (Figure 14e). [298] In the spray coating method, MXene-based ink is sprayed on a substrate, and the shape of the electrode is controlled by a clip of a fixed width. For example, Couly et al adjust the shape by hairpins.…”
Section: Configurations Of Supercapacitorsmentioning
confidence: 99%